IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Kasus di PT. Tambak Seribu Teluk Pandan Pesawaran) - Rudi Wijaya, Muhammad (Institut Agama Islam Negeri Padangsidimpuan, 2018)
Corporate Social Responsibility is one form of social responsibility firm by means running a business that meet the expectations of ethical and legal, set by the government and force in the community. Corporate Social Responsibility (CSR ) it is showing concern it to the interests of the group wider ( stakeholders ) than just a concerned. own company interests here how the researchers want to know (CSR) Corporate Social Responsibility in PT. Tambak Seribu. The study aimed to identify the Corporate Social Responsibility (CSR ). conducted by PT. Tambak Seribu Teluk Pandan Pesawaran. The research is expected to produce an aspiration to increase knowledge of the Corporate Social Responsibility (CSR) As well as expected to benefit managers and employees P.T. Tambak Seribu in fishponds apply the program Corporate Social Responsibility (CSR)Â so that it conforms to The problems faced by the community. The kind of research is field research is descriptive. qualitative for the data collection techniques used, interview documentation and. observation than data-data collected analysis using inductive way of thinking. The result showed that the Corporate Social Responsibility (CSR) PT. Tambak Seribu Teluk Pandan Pesawaran performed in some form covering, holiday assistance, health assistance, scholarships development assistance of, facilities and public facilities handling waste held, the preservation of, clean water and mangrove planting.PT. Tambak SeribuÂ set a budget for CSR thousand farms of 2 % of its profit the year 2014. But realization Corporate Social Responsibility (CSR) by PT. Tambak Seribu technically farms has not yet seen the achievements in the field of, because its achievements CSR more cash for, community assistance the program is not economic partnership with the community and no openness company pertaining to. funds provided to the public CSR, utilizing the momentum of the feast and filing, a proposal by the community so the company seem less proactive in choosing information about the needs of the people who have helped with CSR.